2022
DOI: 10.1016/j.lanepe.2021.100287
|View full text |Cite
|
Sign up to set email alerts
|

Anti-spike antibodies and neutralising antibody activity in people living with HIV vaccinated with COVID-19 mRNA-1273 vaccine: a prospective single-centre cohort study

Abstract: Background Vaccines against COVID-19 are a powerful tool to control the current SARS-CoV-2 pandemic. A thorough description of their immunogenicity among people living with HIV (PLWHIV) is necessary. We aimed to assess the immunogenicity of the mRNA-1273 vaccine among PLWHIV. Methods In this prospective cohort, adult PLWHIV outpatients were enrolled during the Italian vaccination campaign. Enrolment was allowed irrespective of ongoing combination antiretroviral therapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
47
2

Year Published

2022
2022
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(55 citation statements)
references
References 20 publications
6
47
2
Order By: Relevance
“…Furthermore, our multivariate linear regression analysis adjusting for age as well as gender, prime-boost interval, and time after second vaccine dose reveals an effect of HIV-1 infection on serum anti-spike IgA and neutralizing antibody levels but not on anti-spike IgG levels. Our findings are different from other studies reporting similar BNT162b2 mRNA-induced serum anti-spike neutralizing antibody levels between HIV-1-infected persons and healthy controls [ 5 , 7 , 40 , 41 ]. Differences in sampling time could account for divergence in findings, with our sampling time up to 7.5 weeks in HIV-1-infected and 9.5 weeks in HIV-1-uninfected as opposed to 1–4 weeks.…”
Section: Discussioncontrasting
confidence: 99%
“…Furthermore, our multivariate linear regression analysis adjusting for age as well as gender, prime-boost interval, and time after second vaccine dose reveals an effect of HIV-1 infection on serum anti-spike IgA and neutralizing antibody levels but not on anti-spike IgG levels. Our findings are different from other studies reporting similar BNT162b2 mRNA-induced serum anti-spike neutralizing antibody levels between HIV-1-infected persons and healthy controls [ 5 , 7 , 40 , 41 ]. Differences in sampling time could account for divergence in findings, with our sampling time up to 7.5 weeks in HIV-1-infected and 9.5 weeks in HIV-1-uninfected as opposed to 1–4 weeks.…”
Section: Discussioncontrasting
confidence: 99%
“…Data on mRNA vaccines in people living with HIV-1 have been conflicting. 10 , 11 In a prospective, open-label study on the BNT162b2 mRNA vaccine (Pfizer–BioNTech), adjusted analyses revealed that people living with well controlled HIV-1 (n=143) developed neutralising antibody responses that were 33% lower than those in healthy HIV-negative controls (n=261). 10 By contrast, in a small prospective cohort study of the mRNA-1273 vaccine (Moderna), people living with HIV-1 who were SARS-CoV-2-naive (n=62) developed similar neutralising antibody responses to SARS-CoV-2-naive HIV-negative controls; however, the sample size of HIV-negative controls was small (n<10).…”
Section: Discussionmentioning
confidence: 99%
“… 10 By contrast, in a small prospective cohort study of the mRNA-1273 vaccine (Moderna), people living with HIV-1 who were SARS-CoV-2-naive (n=62) developed similar neutralising antibody responses to SARS-CoV-2-naive HIV-negative controls; however, the sample size of HIV-negative controls was small (n<10). 11 In another small, observational study of the BNT162b2 vaccine, the magnitude of SARS-CoV-2-binding antibodies and breadth of neutralising antibody responses to different variants of concern and breadth of T-cell responses were similar in baseline SARS-CoV-2-seronegative people living with HIV-1 (n=12) and in baseline SARS-CoV-2-seronegative HIV-negative participants (n=17); however, the sample size was small and the magnitudes of neutralising antibody responses observed were similarly low for both groups across all strains. 9 A further small, uncontrolled, non-randomised study of two mRNA vaccines in 14 people living with HIV-1 (five with the BNT162b2 vaccine and nine with the mRNA-1273 vaccine) reported detectable but variable anti-receptor-binding-domain IgG titres after a single dose, and a further uniform increase in antibody titres in all 14 people living with HIV-1 after two doses of either vaccine; however, baseline SARS-CoV-2 status was not measured.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[88] In a prospective cohort study which enrolled patients living with HIV (with or without anti-retroviral therapy) with stable viral suppression and robust CD4+ T cell counts, two doses of mRNA-1273 (4 weeks apart) gave rise to humoral immune response at the same level as those without HIV infection. [89] HIV+ individuals with CD4 counts >350 cells/mm 3 also demonstrate humoral and cellular responses similar to control groups after ChAdOx1 nCoV-19 vaccination, with no increase in adverse events frequency. [31] The NVX-CoV2373 COVID-19 vaccine, which in late 2021 and early 2022 was granted emergency use authorization for use in the general population by multiple regulatory authorities including the EMA, [90] is a protein subunit vaccine which could offer an alternative in certain populations.…”
Section: Immunocompromised Patientsmentioning
confidence: 88%